Shark fisheries in Central America a review and update (ESP) - Rojas M., José Rodrigo; Campos M., Jorge; Segura, Álvaro; Mug V., Moisés; Campos, Raúl; Rodríguez, Omar (Uniciencia, 2000)
The demand for shark products especially fins and cartilage, has led to an expansion in fisheries and trade throughout the region. Increased fishing efforts, scarce biological data, and lack of management are key factors that negatively impact this fishery. A project under way aims to gather basic information on population status, nursery and fishery grounds, socioeconomics of the fishery, and necessary conservation measures. Twenty four commercially valuable species have been identified. The most important are Carcharhinus falciformis and Nasolamia velox (Guatemala), C. falciformis (Nicaragua), C. falciformis and M. dorsalis (Costa Rica), C. obscurus (El Salvador), and C. limbatus (Panama). Commercial products include the meat, fin, oil, cartilage, and skin. Shark fins are the most valuable product (i.e. dried caudal fins sell from $US 150 to 400 per kg in Costa Rica) and are exported to Hong Kong, Taiwan, Japan, and the United States.